Podargiform affinities of the enigmatic Fluvioviridavis platyrhamphus and the early diversification of Strisores ("Caprimulgiformes" + Apodiformes). - Sterling J Nesbitt (Public Library of Science (PLoS), 2011)
Background The early Eocene Green River Formation avifauna preserves exceptional exemplars of the earliest unambiguous stem representatives of many extant avian clades. We identify the basal-most member of Podargiformes (extant and fossil stem lineage frogmouths) based on a new specimen of Fluvioviridavis platyrhamphus, a unique neoavian bird from the Fossil Butte Member of the Green River Formation of Wyoming. Extant frogmouths (Podargidae) comprise approximately 13 nocturnal species with an exclusively Australasian distribution. Methodology/principal findings The new specimen was included in a combined phylogenetic analysis of morphological (osteology and soft tissue) and molecular sequence (cytochrome b, c-myc exon 3, and RAG) data sampling species-level taxa from both extant and extinct members of Steatornithidae, Podargidae, Caprimulgidae, Nyctibiidae, Aegothelidae, and Apodiformes ( = Strisores). New data from F. platyrhamphus help resolve phylogenetic relationships within Strisores, supporting placement of F. platyrhamphus and the European fossil form Masillapodargus longipes as basal parts of Podargiformes and also supporting a sister taxon relationship between Podargiformes and Steatornithiformes (oilbirds) within Strisores. This relationship is recovered only when fossil taxa are included, reaffirming the potential impact of stem fossil taxa on inferences of phylogenetic relationships. The well-preserved mandible and palate of the new specimen demonstrate that many of the unique characteristics of the skull that characterize the crown frogmouth clade Podargidae arose early in the evolutionary history of the clade, over 50 million years ago. Comparisons with the new specimen also indicate that Eurofluvioviridavis and Fluvioviridavis are not closely related. Conclusions/significance Together with the European fossil frogmouth Masillapodargus, Fluvioviridavis shows that Podargiformes had a much wider geographic distribution in the past, whereas extant species are restricted to Australasia. The Eocene record of Strisores from the Green River Formation and Messel Formation indicates most major subclade divergences had already occurred by the early-middle Eocene.